PENGEMBANGAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM - Aprilia, Nurul; Fadhli Rabbi, Mim; Cahyadi, Ani (Berajah Journal, 2024)
Islamic Religious Education (PAI) learning. The development of PAI teaching materials is not only focused on knowledge about the Islamic religion but also on various elements of life such as morals and morals of students because the current challenges are the increasingly rapid flow of globalization or science and technology which is inversely proportional to the decline in IMTAQ, and this is a serious challenge to teachers in developing Islamic Religious Education teaching materials. This research is library research (Library Research) which uses a qualitative approach by collecting data in the form of literature studies and using content analysis methods. The research results show that learning will be more interesting for students if the development of teaching materials is in accordance with their needs, does not make them bored, increases learning motivation, and becomes a solution for students in developing their abilities, both in terms of science and technology and faith and piety.